A multination study of socioeconomic inequality in expectations for progression to higher education: the role of between-school tracking and ability stratification - Philip D. Parker; John Jerrim; Ingrid Schoon; Herbert W. Marsh (American Educational Research Journal, 2016)
Persistent inequalities in educational expectations across societies are a growing concern. Recent research has explored the extent to which inequalities in education are due to primary effects (i.e., achievement differentials) versus secondary effects (i.e., choice behaviors net of achievement). We explore educational expectations in order to consider whether variations in primary and secondary effects are associated with country variation in curricular and ability stratification. We use evidence from the PISA 2003 database to test the hypothesis that (a) greater between-school academic stratification would be associated with stronger relationships between socioeconomic status and educational expectations and (b) when this effect is decomposed, achievement differentials would explain a greater proportion of this relationship in countries with greater stratification. Results supported these hypotheses.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; educational expectations; educational inequality; primary and secondary effects; curricular tracking; ability stratification